Sola Scriptura: biblical and theological perspectives on scripture, authority, and hermeneutics - Burger, Hans; Huijgen, Arnold; Peels, H. G. L. (Studies in Reformed Theology Ser, 2017)
Sola Scriptura offers a multi-disciplinary reflection on the theme of the priority and importance of Scripture in theology, from historical, biblical-theological and systematic-theological perspectives, aiming at the interaction between exegesis and dogmatics.